On-surface synthesis of non-benzenoid conjugated polymers by selective atomic rearrangement of ethynylarenes. Issue 6 (5th January 2023) - Jiménez-Martín, Alejandro; Villalobos, Federico; Mallada, Benjamin; Edalatmanesh, Shayan; Matěj, Adam; Cuerva, Juan M.; Jelínek, Pavel; Campaña, Araceli G.; de la Torre, Bruno
Abstract : Here, we report a new on-surface synthetic strategy to precisely introduce five-membered units into conjugated polymers from specifically designed precursor molecules that give rise to low-bandgap fulvalene-bridged bisanthene polymers. Abstract : Here, we report a new on-surface synthetic strategy to precisely introduce five-membered units into conjugated polymers from specifically designed precursor molecules that give rise to low-bandgap fulvalene-bridged bisanthene polymers. The selective formation of non-benzenoid units is finely controlled by the annealing parameters, which govern the initiation of atomic rearrangements that efficiently transform previously formed diethynyl bridges into fulvalene moieties. The atomically precise structures and electronic properties have been unmistakably characterized by STM, nc-AFM, and STS and the results are supported by DFT theoretical calculations. Interestingly, the fulvalene-bridged bisanthene polymers exhibit experimental narrow frontier electronic gaps of 1.2 eV on Au(111) with fully conjugated units. This on-surface synthetic strategy can potentially be extended to other conjugated polymers to tune their optoelectronic properties by integrating five-membered rings at precise sites.